2015
DOI: 10.1039/c5ra20885h
|View full text |Cite
|
Sign up to set email alerts
|

On the structure of high performance anticorrosive PMMA–siloxane–silica hybrid coatings

Abstract: Environmentally compliant organic–inorganic hybrid coatings for efficient corrosion protection of metallic surfaces are potential alternatives to the current method based on chromate passivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
99
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 21 publications
(47 reference statements)
12
99
2
Order By: Relevance
“…More specifically, regarding the epoxy-silica hybrid system, the results presented in this work and those listed in Table 7 show that different compositions applied to distinct alloys can provide a very effective long-term corrosion protection [7,26,27]. Very promising results were also achieved for PMMA-silica coatings [8,10,31], with the highest observed durability of more than 560 days in 3.5% NaCl, and for hybrids containing reinforcement and inhibitor agents [11,18]. Moreover, for some polyurethane-silica and polyurethane-zirconia-silica systems, it has been demonstrated that they also have a high potential to be used as efficient anticorrosive barrier layers [9,32].…”
Section: Advances In Organic-inorganic Hybrid Coatings For Corrosion mentioning
confidence: 49%
See 4 more Smart Citations
“…More specifically, regarding the epoxy-silica hybrid system, the results presented in this work and those listed in Table 7 show that different compositions applied to distinct alloys can provide a very effective long-term corrosion protection [7,26,27]. Very promising results were also achieved for PMMA-silica coatings [8,10,31], with the highest observed durability of more than 560 days in 3.5% NaCl, and for hybrids containing reinforcement and inhibitor agents [11,18]. Moreover, for some polyurethane-silica and polyurethane-zirconia-silica systems, it has been demonstrated that they also have a high potential to be used as efficient anticorrosive barrier layers [9,32].…”
Section: Advances In Organic-inorganic Hybrid Coatings For Corrosion mentioning
confidence: 49%
“…After optimizing also the ethanol-to-water ratio of the inorganic phase to a value of 0.2, the corrosion resistance and lifetime were further increase to 196 days in 3.5% NaCl (M8_4h_E0.2 coating, Table 4) [10]. Other important finding was the improvement of the corrosion resistance by hot deposition (M8_T80B0.01), which enhances the reaction between the inorganic phase and the metal substrate, improving the coating adhesion.…”
Section: Pmma-silica Hybridsmentioning
confidence: 85%
See 3 more Smart Citations